BL_GERICHTE 720 2014 363 / 152 vom 11. Juni 2015 , Entscheid des Kantonsgerichts Basel-Landschaft, Abteilung Sozialversicherungsrecht vom 11. Juni 2015 (720 14 363 / 152) - BL Gerichte (2015)
IV-Rente